2018
DOI: 10.1002/ecy.2138
|View full text |Cite
|
Sign up to set email alerts
|

Positive diversity‐functioning relationships in model communities of methanotrophic bacteria

Abstract: we tested effects of biodiversity on the functioning of methanotrophs, a specialized group of soil 27 bacteria that plays a key role in mediating greenhouse gas emissions from soils. Using pure 28 strains of methanotrophic bacteria, we assembled artificial communities of different diversity 29 levels, with which we inoculated sterile soil microcosms. To assess the functioning of these 30 communities, we measured methane oxidation by gas chromatography throughout the 31 experiment and determined changes in comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
2
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 75 publications
1
21
2
3
Order By: Relevance
“…In contrast to diversity experiments in which artificial communities are assembled de novo from isolated strains [45], dilution treatments decrease the abundance of both target and non-target microorganisms, and our study was no exception. However, soil communities recovered well during the 4-week preincubation, with no remaining differences in total bacterial and only relatively small differences in methanotrophic community size at day zero except for the most diluted community which required more time to recover.…”
Section: Discussioncontrasting
confidence: 66%
See 2 more Smart Citations
“…In contrast to diversity experiments in which artificial communities are assembled de novo from isolated strains [45], dilution treatments decrease the abundance of both target and non-target microorganisms, and our study was no exception. However, soil communities recovered well during the 4-week preincubation, with no remaining differences in total bacterial and only relatively small differences in methanotrophic community size at day zero except for the most diluted community which required more time to recover.…”
Section: Discussioncontrasting
confidence: 66%
“…Headspace air was pumped through a heat exchanger that equilibrated the gas to room temperature. Then, the sampled air was dried in a tube filled with silica gel beads before CH 4 concentrations were determined in a CH 4 using a customized pipeline [45] that based on the algorithms implemented in USEARCH v9 [69]. All pmoA OTU sequences were blasted against the NCBI database and sequences that did not yield a match or were not pmoA were removed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3], suggesting that there is a need for variables that increase the accuracy of biological processes [4]. 14 The development of a more mechanistic picture is hindered for several reasons, such as diculties in identi-15 fying the relative role of stochastic and deterministic processes in shaping microbial communities [5,6,7], the 16 pervasiveness of functional redundancy [8,9], and of priority eects [10]. In addition, it is often dicult to 17 identify which functions to assess.…”
Section: Introductionmentioning
confidence: 99%
“…The abundance of these 75 markers is often hypothesized to be predictive of the rate of their associated processes (for example, the 76 abundance of mcrA is often hypothesized to be related to the rate of methanogenesis). There are 77 examples where this relationship is present (12)(13)(14). However, a review of such studies found that the 78 abundance of a functional gene or transcript is rarely correlated with the rate of the corresponding 79 process and depends on the function of interest, with most effects either negative or not significant (4).…”
Section: Traditional Approaches To Quantifying This Relationship Havementioning
confidence: 99%